Upaya Guru dalam Menanggulangi Kesulitan Siswa Menghafal al-Qur’an di SD IT Hasanah Kecamatan Pantai Cermin - Selvi Tria Ananda; Rahmi Wiza (Lembaga Yasin AlSys, 2026)
Although studies on teachers’ efforts to address students’ difficulties in memorizing the Al-Qur’an have been conducted previously, discussions that specifically highlight these efforts through structured evaluation remain limited. This study aims to examine the forms of students’ difficulties in memorizing the Al-Qur’an at SD IT Hasanah, Pantai Cermin Subdistrict, as well as the efforts made by teachers to address them through various forms of evaluation. This study used a qualitative method with a case study type. The data sources were obtained from informants selected through purposive sampling, and were supported by primary and secondary data. Data were collected through non-participant observation, semi-structured interviews, and documentation, and were then analyzed using the Miles, Huberman, and Saldana model through the stages of data condensation, data display, and conclusion drawing. The results showed that students’ difficulties in memorizing the Al-Qur’an included low motivation, lack of seriousness, infrequent muraja’ah, and not yet optimal mastery of makharijul huruf and tajwid. In addressing these difficulties, teachers applied context, input, process, and outcome evaluation. These findings indicate that structured evaluation can be an effective way to improve students’ Al-Qur’an memorization ability, shape religious and disciplined character, and serve as a reference for teachers in carrying out tahfiz activities sustainably. This study emphasizes the importance of continuous evaluation in addressing students’ difficulties in memorizing the Al-Qur’an and opens opportunities for further research on the role of parents in assisting students’ memorization at home.